Online interaction of Olympic volunteers after the Games - M. P. Sukharkova (Цифровая социология, 2021)
The article is devoted to the community of Olympic volunteers after the event through the study of their online activity in social network “Vkontakte”. Olympic volunteering refers to the event-oriented direction of volunteering, which is characterized by a limited period of time for the implementation of volunteering practices, but a long period of training volunteers and the opportunity for volunteers to acquire unique work experience during the organization and holding of a major sports event. At the moment, there is a lack of research on the impact of events such as the Olympic and Paralympic Games on the volunteer community.The legacy of the 2014 Olympic and Paralympic Games for the volunteer community is studied in the article. In the course of the study, an attempt was made to find answers to the following research questions: do volunteers maintain social online interactions five or more years after the event; if volunteers continue online interactions, what topics are the most popular for discussion in the volunteer community. It is proved that volunteering at major sporting events contributes to the development of the social capital of volunteers, including by expanding the circle of acquaintances, that is, social interactions. At the same time, social networks have a great influence on the reproduction of social capital, so the indicators of online interactions of volunteers can indicate whether the volunteers support the circles of social interactions acquired while working at the games, and, thus, whether the volunteers support and use the social capital acquired while working at the event. During the entire period of time considered by us, the highest indicators of volunteer activity in the online community were noted from 2014 to 2016. The most relevant topics among the participants of the online community are the topics of volunteering: both memories of working at the games, as well as information about other volunteer programs and other topics, for example, tourism, etc.